A river runs through it : the restoration of environmental integrity & community upliftment through sustainable dam development - based on the Berg River Dam - Sole, Kerry-Ann (School of Architecture, Planning and Geomatics, 2014)
Dams capture floodwater in reservoirs and release it during dry periods, sustaining life through droughts. They allow communities to be self-sufficient through irrigation, generate power and provide health and prosperity increasingly in the developing world. Historically, people have believed that water which flows into the sea is “wasted” and therefore must be intercepted for human use. This attitude, enforced by an ever-increasing demand for water by a growing population in a dry country, has largely fuelled the need for river impoundment in South Africa. Given the reality of the country's severe 'water-crisis', it is deemed necessary to collect water in large enough amounts to safe-guard a sufficient supply of water both in dry summer months and years of drought. In line with the country's constitution, access to clean water for drinking, health and sanitation is one of the major world development issues and central to poverty alleviation [58]. Through time, large dams have emerged as one of the most significant and visible tools for the management of water resources. However, construction of this kind has severe impacts. In the persistent goal to achieve a secure water-supply, the conservation of nature and her environs has been neglected in many cases. Furthermore, this conservation is primarily a long-term process, often in direct conflict to the immediate needs of man. The Berg River Dam is currently under construction just outside the town of Franschhoek in the Western Cape. Intended to supply drinking water to thousands, the Berg River Dam represents a promise to plenty. Once completed, this project will constitute one of the largest of its kind in South Africa. Development associated with the Berg River Dam is due to take place. Given the context of the place, the type of development necessary is debatable. Various stakeholders from all walks of life are involved, all determined to seek what the Dam has to offer in terms of 'benefits'. This projects is a journey to discover the true meaning behind dams, their developments and pledged 'benefits', and to determine what is appropriate in this locality.